Granulocyte colony‐stimulating factor‐associated aortitis in a man with advanced prostate cancer - Ryota Ikadai; Goshi Kitano; Manabu Kato; Takahiro Kojima (IJU Case Reports)
Introduction Granulocyte colony‐stimulating factor‐associated aortitis remains poorly understood among clinicians. Case presentation We present a case of G‐CSF‐associated aortitis in a 70‐year‐old male with stage IVb castration‐resistant prostate cancer (cT3bN0M1b) receiving docetaxel chemotherapy. Neutropenia (280/μL) developed on day 8 of the first chemotherapy cycle, prompting subcutaneous administration of filgrastim, a short‐acting G‐CSF, on days 8–10. On day 14, the patient presented to the outpatient clinic with fever but no other significant symptoms. Computed tomography revealed filgrastim‐induced thoracic aortitis. Daily prednisone treatment (equivalent to 25 mg prednisolone) was initiated on the following day. Although the initial episode of aortitis resolved within 5 weeks, subsequent pegfilgrastim resulted in recurrence around the left subclavian artery, necessitating further steroid therapy. Conclusion Persistent high fever following G‐CSF administration may indicate drug‐induced aortitis, highlighting the potential for aortitis recurrence with repeated G‐CSF use.